The Effect of Board Characteristics and Financial Performance on Sustainability Disclosure - Arifin, Muhammad Ferdy; Rasuli, Muhammad; Khoiriyah, Mayla (Jurnal Riset Akuntansi Terpadu, 2025)
This study aims to determine and analyse the influence of female board leadership, board independence, board financial expertise, and return on assets on sustainability disclosure. This research is quantitative research with multiple linear regression analysis method. The population in this study are companies listed on the Indonesia Stock Exchange in 2019-2022. The sample used in this study was obtained as many as 91 companies using purposive sampling. The sample criteria in this study are companies listed on the Indonesia Stock Exchange in 2019-2022, companies that do not have ESG disclosure in 2019-2022, and companies that do not have complete annual reports and sustainability disclosures in 2019-2022. The data collection technique in this study is secondary data. The results showed that female board leadership has a positive effect on sustainability disclosure, board independence and financial performance have a negative effect on sustainability disclosure. And financial performance as measured using return on assets has a positive effect on sustainability disclosure.